Synthesis and Characterization of Conductive Copolymer/MWCNT Nanocomposite via Chemical and Interfacial Polymerization - Hajer A. Hussein; Mohammed Q Mohammed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Various monomers were employed to synthesize copolymers, followed by the fabrication of nanocomposites through the incorporation of 1% carboxyl-functionalized multi-walled carbon nanotubes (MWCNTs–COOH). These nanotubes were modified in the laboratory to enhance the interaction between the polymer matrix and the nanotubes.  The nano-doping has led to improve the electrical and thermal performance of the producte materials. The FTIR, XRD, TGA, SEM, and EDX were utilized to characterized composites, while electrical conductivity was measured using the pellet method. The results revealed that the incorporation of functionalized MWCNTs led to significant improvements in electrical conductivity, thermal stability, and morphological structure of the copolymer systems, highlighting their potential for advanced electronic and optoelectronic applications.